PEDAGOGICAL FEATURES OF THE FORMATION OF SOCIALLY ACTIVE PERSONALITY QUALITIES IN GIRLS (Scientific journal of the Fergana State University, 2023)
This article analyzes such directions as the development of healthy and harmonious development of girls in our country, the realization of their creative and intellectual potential, pedagogical aspects of the formation of socially active personality qualities, the development of legislation in their social protection.